Rancang Bangun Energi Matahari 300 WP Sebagai Suport Energi Listrik untuk Sistem Energi Hybrid - Suripto, Heri (Accurate: Journal of Mechanical Engineering and Science, 2021)
Hybrid energy having continuous development considering the energy needs continue to increase. As the development continues, the use of alternative energy becomes a solution in overcoming energy needs. This research will be designig and manufacturing solar energy as a support for electrical energy used for a hybrid system based on solar and hydro energy. From the results of the design of the solar cell module holder frame, it produces specifications for a height of 100 cm, a width of 67 cm and a length of 90 cm, from the calculation, the pump electric energy consumption of a 125 watt32 liters / minute to fill a 1000 liter water tank is 66.7 watts, the solar cell power calculation is 33.6 watts per unit, so that the number of solar cell modules needed is 2, the design of the solar cell module made is 3 units, 1 unit is used as electrical energy saving. The test results based on solar radiation, the average solar radiation intensity is 4916 (watt/m2) with a power of 19.76 watts.